Electrospun PLA/Cellulose/Chitosan/PEG Nanofibers for Wound Dressing: Effects of Composition and Feed Rate - Shofiyah; Syis Muhim; Srie Muljani; Tri Widjaja; Aisyah Alifatul Zahidah Rohmah; Citra Yulia S ari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study presents the development of a biocompatible and biodegradable nanofiber-based wound dressing fabricated via electrospinning using a composite of polylactic acid (PLA), cellulose, chitosan, and polyethylene glycol (PEG). The novelty of this work lies in the systematic control of material composition and processing parameters, particularly the feed rate, to regulate fiber morphology and surface properties. The results demonstrate that the incorporation of PEG, cellulose, and chitosan influences the contact angle through intermolecular hydrogen bonding, without forming new chemical bonds, indicating that physical blending rather than chemical interactions govern the system. Furthermore, increasing the feed rate enhances polymer jet stretching, resulting in finer and more uniform nanofibers. The resulting nanofiber structure exhibits characteristics suitable for wound dressing applications, including improved interaction with aqueous environments and structural uniformity. Overall, this study provides insight into the relationship between material composition, processing conditions, and nanofiber formation mechanisms, contributing to the rational design of advanced biomaterials for biomedical applications. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action